Irritable Bowel Syndrome and its Homoeopathic Management - A Review - M. Kannan; J. Kathiravan (AYUSHDHARA, 2022)
Irritable bowel syndrome is a functional gastrointestinal disease with high population prevalence. The disorder can be debilitating in some patients, whereas others may have mild or moderate symptoms. It considerably affects quality of life and imposes a profound burden on patients, physicians and the health-care system. The condition has considerable consequences for quality of life (QOL) that are comparable to other chronic diseases, such as diabetes mellitus and hepatitis. Patients with the disorder have been consistently shown to have poor health-related quality of life (HRQOL). This disorder accounts for significant healthcare costs. In addition to direct medical expenses, costs to society come in the form of work absenteeism and impaired work productivity. The review aims to seek the scope of homoeopathy in the management of irritable bowel syndrome. The principles and practice of homoeopathic treatment overlap across these aspects of IBS for it prioritizes patient’s subjective mental symptoms and seeks to provide tailored treatment for each individual patient.